Tingkat Pengetahuan Mahasiswa Keperawatan Tentang Kode Etik Profesi dan Caring - Selvyyanny Tedjomuljo; Efy Afifah (Jurnal Keperawatan Indonesia, 2016)
Kode etik dan caring harus diketahui oleh mahasiswa keperawatan karena kedua hal tersebut merupakan dasar dari profesi keperawatan. Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan tentang kode etik keperawatan dan caring pada mahasiswa keperawatan. Jenis penelitian ini adalah deskriptif dengan pendekatan cross sectional pada 226 mahasiswa keperawatan melalui teknik simple random sampling. Hasil penelitian menunjukkan bahwa mahasiswa keperawatan memiliki tingkat pengetahuan yang baik (92%) mengenai kode etik secara umum dan cukup (47,3%) mengenai caring. Institusi pendidikan keperawatan diharapkan dapat memberikan edukasi dan memotivasi mahasiswa untuk mempraktikkan pengetahuan kode etik dan caring yang telah diberikan dalam kehidupan sehari-hari. Abstract Level of Knowledge Nursing Students about Code of Ethics Profession and Caring. Nursing students have to know about code of ethics and caring because both of them are fundamental on nursing profession. This study used to know a representation of the level of knowledge of the nursing profession's code of ethics and caring among nursing students in Universitas Indonesia. This study used decriptive with cross sectional approach among 226 nursing students University of Indonesia by using simple random sampling methods. The results showed that nursing student in Universitas Indonesia (92%) has a good level of knowledge of the nursing profession's code of ethics and (47,3%) respondents has a fair level of knowledge of caring in the nursing profession. It was recommended for nursing faculty to give education and motivate students to practice the knowledge of the nursing profession's code of ethics and caring in daily activities. Keywords: caring, code of ethics level of knowledge, nursing faculty, nursing students